Dielectric Properties of Polymethylmethacrylate and Its Composites with ZnO - Sannakki, Basavaraja; Nivrtirao, Eknath (Asian Journal of Chemistry, 2011)
The polymer films of polymethylmethacrylate at different thickness and its composites with ZnO at various weight percentages of same thickness have been studied for the determination of dielectric properties, dielectric loss, A.C. conductivity and dielectric modulus using measurements of capacitance of the above samples as a function of frequency over the range 50 Hz-5 MHz at room temperature. The films of polymethylmethacrylate and its composites have been characterized using X-ray diffractometer. The dielectric permittivity of films of polymethylmethacrylate behaves nonlinearly as frequency increases over the range 50-300 Hz, where as above 300 Hz the values of dielectric constant remain constant. But it is observed that the dielectric constant of polymethylmethacrylate increases as thickness of the film increases. In case of composite films of polymethylmethacrylate with ZnO the values of dielectric permittivity decreases gradually up to frequency of around 1 KHz and at higher frequencies it remains constant for all the weight percentages of ZnO. But it is observed that the properties of dielectric constant decrease as weight percentage of the compound increases. The complex form of dielectric modulus of polymethylmethacrylate is obtained from the experimentally measured data of dielectric constant and dielectric loss values. The relaxation time of the orientation of dipoles is obtained from the peak value of angular frequency through the plots of imaginary part of electrical modulus as function of frequency. The impedance of polymethylmethacrylate polymer increases as thickness of the films increases. The A.C. conductivity of polymethylmethacrylate film remains constant up to frequency of 1 MHz and above this it shows a nonlinear phenomena with peak values at frequency 4 MHz.